2010
DOI: 10.1371/journal.pone.0015653
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 Treatment Reduces Inflammation but Does Not Prevent Ventilator-Induced Lung Injury

Abstract: BackgroundLoss of integrity of the epithelial and endothelial barriers is thought to be a prominent feature of ventilator-induced lung injury (VILI). Based on its function in vascular integrity, we hypothesize that the angiopoietin (Ang)-Tie2 system plays a role in the development of VILI. The present study was designed to examine the effects of mechanical ventilation on the Ang-Tie2 system in lung tissue. Moreover, we evaluated whether treatment with Ang-1, a Tie2 receptor agonist, protects against inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 42 publications
5
38
1
1
Order By: Relevance
“…Moreover, we observed that HV T -ventilation caused increased expression of VEGF (figure 4g) which is in agreement with a prior report (Nin et al, 2008). Our findings strongly suggest that changes in the Ang-Tie2 system, together with elevated VEGF expression, are involved in the development of VILI (Hegeman et al, 2010). Fig.…”
Section: Loss Of Vascular Integritysupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, we observed that HV T -ventilation caused increased expression of VEGF (figure 4g) which is in agreement with a prior report (Nin et al, 2008). Our findings strongly suggest that changes in the Ang-Tie2 system, together with elevated VEGF expression, are involved in the development of VILI (Hegeman et al, 2010). Fig.…”
Section: Loss Of Vascular Integritysupporting
confidence: 93%
“…However, even in our relatively mild model of VILI, mechanical ventilation with either low (LV T ) or high tidal volumes (HV T ) caused increased cytokine, chemokine and adhesion molecule expression compared to non-ventilated control (NVC) animals, which was accompanied by marked granulocyte infiltration (Hegeman et al, 2011b). BALf neutrophil numbers and inflammatory mediator levels were even higher when comparing lungs of HV T -ventilated mice to lungs of LV T -ventilated mice (Hegeman et al, 2011b). Since lower PaO 2 /FiO 2 ratios were only observed after HV T -ventilation, it seems plausible that ventilator-induced lung inflammation ultimately impairs gas exchange.…”
Section: Inflammatory Responsementioning
confidence: 74%
See 3 more Smart Citations